MySchool Application as a Computer-mediated Communication for Parents, School, and Teachers - Yocbahawie, Bobby; Yudhistira, Naftali; Sumbodo, Mugiatno (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2020)
School is a very important place for every individual and also the primary center of a smart nation generation where the teaching and learning process is carried out continuously every day. In the teaching and learning process, communication between parents and schools plays a very important role because students’ academic success cannot be separated from the support of their parents, currently parents and schools usually create WhatsApp Groups (WAGs) to establish communication whose purpose is to find out about activities students in school such as: attendance, student grades, exam schedule, important announcements, and others. Moreover, the Covid-19 Pandemic adds to the series of problems that must be resolved and immediately sought for solutions together. For this reason, a system is needed to overcome these problems through the use of information technology in the communication process between parents and schools. MySchool application aims to solve communication problems between parents, teachers, and schools, besides this application also aims to support the school administration system in such as tuition fees, information on school activities, important announcements, and others. This application is also a series of solutions for the teaching and learning processes of school activities during the Covid-19 pandemic and by optimizing it can convert all activities to be completely digital ones. The feedbacks were very positive like having mobile app as a mean of communication at school provides effective relationship between parents and the school.